Comparison between open and laparoscopic elective cholecystectomy in elderly, in a teaching hospital - Rubert,Cássio Padilha (2016)
Objective: to analyze the differences in mortality rates, length of hospital stay, time of surgery and the conversion rate between elective open cholecystectomies (OC) and laparoscopic ones (LC) in elderly patients. Methods : we evaluated medical records of patients 65 years of age or older undergoing open or laparoscopic cholecystectomy at the Hospital Regional de Mato Grosso do Sul between January 2008 and December 2011. We excluded individuals operated in non-elective scenarios or who underwent intraoperative cholangiography. Results : we studied 113 patients, of whom 38.1% were submitted to the OC and 61.9%, to LC. Women accounted for 69% of patients and men, for 31%. The conversion rate was 2.9%. The mean age and duration of the procudure was 70.1 and 84 minutes, respectively, with no significant difference between OC and LC. Patients undergoing LC had shorter hospital stays (2.01 versus 2.95 days, p=0.0001). We identified operative complications in sixpatients (14%) after OC and in nine (12%) after LC, with no statistical difference. Conclusion : there was no difference in morbidity and mortality when comparing OC with LC. The laparoscopic approach led to shorter hospital stay. Operative time did not differ between the two access routes. The conversion rate was similar to other studies.